2002
DOI: 10.1002/art.10128
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive expression of BCL‐XL in the T lineage attenuates collagen‐induced arthritis in Bcl‐XL transgenic mice

Abstract: Objective. To determine if inhibition of T cell apoptosis through constitutive expression of Bcl-x L in the T lineage influences inflammatory arthritis in the mouse collagen-induced arthritis (CIA) model.Methods. The incidence and severity of arthritis were quantified in Bcl-x L transgenic mice and nontransgenic littermates after immunization with type II collagen (CII). To correlate T cell responses with disease phenotype, antigen-specific T cell proliferation was measured by 3 H-thymidine incorporation. Apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In agreement with our present study, it has been described recently that the constitutive Tg expression of Bcl-x L in T cells attenuates the development of CIA (42). Although the authors of this study do not clarify the mechanism directly involved in such protective effect, due to the similarities between Bcl-2 and Bcl-x L in the regulation of programmed cell death, and more particularly in the regulation of lymphocyte survival (3,43), it is likely that analogous mechanisms account for the protection against CIA in both Bcl-x L T cell Tg and Bcl-2 Tg2 mice.…”
Section: Cd25supporting
confidence: 94%
“…In agreement with our present study, it has been described recently that the constitutive Tg expression of Bcl-x L in T cells attenuates the development of CIA (42). Although the authors of this study do not clarify the mechanism directly involved in such protective effect, due to the similarities between Bcl-2 and Bcl-x L in the regulation of programmed cell death, and more particularly in the regulation of lymphocyte survival (3,43), it is likely that analogous mechanisms account for the protection against CIA in both Bcl-x L T cell Tg and Bcl-2 Tg2 mice.…”
Section: Cd25supporting
confidence: 94%
“…Interestingly, one earlier study has shown that T cell lineagespecific expression of Bcl-XL transgene resulted in decreased IFN-␥ production and attenuated CIA (33). Several factors may explain the seemingly contradictory results from these two studies.…”
Section: Discussionmentioning
confidence: 98%
“…Initial studies in CIA mouse models focused on the overexpression of Bcl2 and Bcl-xL in lymphocytes. Results showed that although overexpression of Bcl-xL in B cells exacerbate CIA 126 , in T cells it attenuates the development of arthritis, potentially through their resistance to apoptosis, delayed cell cycle progression and inhibition of IFN-γ production in response to type II collagen challenge 127 . Similarly, overexpression of Bcl2 in all hematopoietic cells reduces the development of CIA, potentially by resulting in decreased production of antibodies against type II collagen 128 .…”
Section: Extrinsic Pathway Of Apoptosis In Ramentioning
confidence: 99%